The Formation of National R&D and Innovation Policy Based on «Triple Helix» (Government–Science–Industry) Extended Model (brief information about the project) - Yegorov, I.Yu. (Science and Innovation, 2024)
Introduction. In recent years, the problem of rational organization of interaction between different stakeholders of the innovation process has become increasingly important. Since the late 1990s, the advanced economies have been paying special attention to the so-called «triple helix» model of interaction in the «science–government–industry» system. Problem Statement. Within the project framework, the evolution of this model has been analyzed, specific features of the formation of appropriate links have been studied, effectiveness assessment criteria and performance indicators for various model «actors» have been identified. Materials and Methods. Methods of statistics, morphological and logical analysis, and comparative studies have been used for the purpose of research. Results. Special attention has been paid to the problems of formation of «triple helix» model in the countries that have been implementing fundamental reforms in their economies. These countries have been shown to have a lack of important institutional elements necessary for successful operation of «triple helix», so the interaction between its individual elements is ineffective or even absent at all. This leads to system disintegration into separate subsystems of «pair interactions» that are not relevant to the processes of consolidation and, in many cases, entails a significant reduction in the overall efficiency of the national innovation system. Conclusion. The final section of the paper contains information about applicability of the «triple helix» model to the Ukrainian realities, identification of the key problems and recommendations regarding the establishment and further development of the core components of the model.